C2C12 Mouse Myoblasts Damage Induced by Oxidative Stress Is Alleviated by the Antioxidant Capacity of the Active Substance Phloretin - Li, Jie; Yang, Qing; Han, Lin; Pan, Chuanying; Lei, Chuzhao; Chen, Hong; Lan, Xianyong (Frontiers in Cell and Developmental Biology, 2020)
A new direction for the treatment of skeletal myopathies, which are mainly caused by abnormal mitochondrial metabolism, is the application of drugs and active substances to relieve oxidative stress in mitochondria. Phloretin, a dihydrochalcone active substance widely present in succulent fruits, has attracted attention for its strong antioxidant activity. This study aimed to investigate the potential antioxidant effects of phloretin and its potential mechanism of action in C2C12 mouse myoblasts. Under oxidative stress caused by 500 µmol/L H2O2, the addition of 10 µmol/L phloretin ameliorated the high level of reactive oxygen species, increased CuZn/Mn-dependent superoxide dismutase activities, and restored the loss of mitochondrial membrane potential. Additionally, apoptosis, necrocytosis, and the inhibition of cell proliferation caused by H2O2 stimulation were alleviated by phloretin. Moreover, phloretin significantly increased the expression of cyclin D1 and alleviated the stagnation trend of the G1 phase of cell proliferation caused by H2O2. Furthermore, the addition of phloretin simultaneously significantly increased the protein and mRNA expression of heme oxygenase-1 (HO-1) and alleviated the inhibitory phosphorylation of p-nuclear factor erythroid 2-related factor 2 (Nrf2), p-AMP-activated protein kinase (AMPK), and p-liver kinase B1 (LKB1) induced by H2O2. Moreover, the expression of nuclear Nrf2 was higher with phloretin treatment than without phloretin treatment. Overall, phloretin alleviated the proliferation inhibition and apoptosis induced by H2O2 and exerted antioxidant effects via the LKB1/AMPK/Nrf2/HO-1 pathway in C2C12 cells. These results provide insight for the application of phloretin to alleviate oxidative damage to muscle.